RANCANG BANGUN PURWA-RUPA CMM TOWER FIXTURE SEBAGAI DASAR MEDIA PEMBELAJARAN GD&T - Wilujeng, Auliana Diah (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
The CMM (Coordinate Measuring Machine) machine is a high-speed, multi-function measuring device that produces high measurement accuracy and efficiency. CMM machines have the advantage of being a high level of precision, accurate, and requires a short measurement time (more efficient). But the disadvantage is the product to be measured must be stationary / static, so it needs a fixture. This problem then requires a tower-shaped fixture to keep the object static. Tower-fixtures are generally rectangular (4 sides). Generally, objects that have a high degree of complexity will need a tower fixture that has more than 4 sides. The brand that provides a buffer tower with more than 4 sides, namely Renishaw, has a fairly expensive price.Product designs are designed and drawn using the SolidWork Software 2013. Products are made using machining processes including using lathes, milling machines, drilling machines, and bench work tools. The product material used is Aluminum 6061. After the finished product, the product will be validated in dimensions using a CMM machine.The results obtained indicate that 64.3% of the total measurement of the tower fixture product is within the permissible tolerance range. The rest, as much as 35.7% of measurements are not acceptable because they exceed the tolerance limit given. This is caused by several factors, including human error and inaccuracies in the machining process, causing a difference in dimensions between the design drawings and the original dimensions of the product.